2005
DOI: 10.1111/j.1464-410x.2005.05344.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability of detrusor overactivity on repeated filling cystometry in men with urge symptoms: comparison with spinal cord injury patients

Abstract: Iversen Symptom Score (MSS), uroflowmetry, filling cystometry and pressure-flow, in three successive studies. RESULTSIn men with LUTS, a significant decrease in the number and pressure of involuntary detrusor contractions (IDCs) in consecutive cystometries resulted in a reduction of observed detrusor overactivity from 72% to 63% and 48%, in the three studies. Urgency scores were significantly lower in men who became 'stable' than in those who remained 'unstable' throughout the three studies. In men with SCI, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 25 publications
0
40
0
1
Order By: Relevance
“…In this context, epidemiology may be especially useful, for example: ageing is associated with a rising prevalence of overactive bladder (OAB) syndrome; 1 bladder outflow tract obstruction (BOO) is associated with a high prevalence of LUTS; 2 neurological lesions are associated with a high prevalence of detrusor overactivity but not necessarily with urgency. 3 (ii) Describe the most useful current, clinical measurements that quantify the clinical problem so that animal data may be used to translate their findings to the human condition. (iii) Describe the aetiology or pathophysiology in human tissues and organs obtained from patients, for example, why does the bladder become overactive or why does the urethral sphincter become insufficient.…”
mentioning
confidence: 99%
“…In this context, epidemiology may be especially useful, for example: ageing is associated with a rising prevalence of overactive bladder (OAB) syndrome; 1 bladder outflow tract obstruction (BOO) is associated with a high prevalence of LUTS; 2 neurological lesions are associated with a high prevalence of detrusor overactivity but not necessarily with urgency. 3 (ii) Describe the most useful current, clinical measurements that quantify the clinical problem so that animal data may be used to translate their findings to the human condition. (iii) Describe the aetiology or pathophysiology in human tissues and organs obtained from patients, for example, why does the bladder become overactive or why does the urethral sphincter become insufficient.…”
mentioning
confidence: 99%
“…For this reason, common examination methods, such as the urodynamics test and the sympathetic skin response, cannot be used in rats. 32,33 In recent years, Blok et al 34 determined bladder function by using positron emission tomography to detect the changes in neuronal excitability of the frontal lobe and cingulate gyrus during bladder filling. It remains to be determined whether this technique can be used in the experiment type described here.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…However, we do not think that repeated cystometries had a major effect on the increased capacity in the intermittent filling cystometry as Thyberg et al (12) found no significant difference between the mean maximum detrusor pressure in the first and second cystometries compared with the third and fourth cystometries, which were performed with 10 minutes intervals between them in a SCI population with overactive detrusors. Similarly, Ockrim et al performed 3 sequential cystometries in men with SCI and reported that cystometric variables and detrusor overactivity remained consistent over sequential studies (13).…”
Section: R Re Es Su Ul Lt Ts Smentioning
confidence: 99%